2014
DOI: 10.1093/ejcts/ezu312
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral pulmonary oedema after minimally invasive cardiac surgery via right anterolateral minithoracotomy

Abstract: Our data revealed a 7.9% incidence of radiographically evident unilateral pulmonary oedema after MICS with intraoperative collapse of a lung. Of the total number of patients, 1.5% simultaneously developed clinical symptoms. The influence of corticosteroids, as well as the contribution of possible risk factors, needs further evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 25 publications
1
32
0
1
Order By: Relevance
“…Furthermore, reports exist of mostly unilateral pulmonary edema after access through right-sided minithoracotomy. Keyl et al described-in a study of 485 patients treated by using minimally invasive surgery-a rate of 7.85% (28). The causes of pulmonary edema, which in practice has been described only for minimally invasive valve surgery, are not known.…”
Section: Anesthesia and Postoperative Care In Minimally Invasive Procmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, reports exist of mostly unilateral pulmonary edema after access through right-sided minithoracotomy. Keyl et al described-in a study of 485 patients treated by using minimally invasive surgery-a rate of 7.85% (28). The causes of pulmonary edema, which in practice has been described only for minimally invasive valve surgery, are not known.…”
Section: Anesthesia and Postoperative Care In Minimally Invasive Procmentioning
confidence: 99%
“…What is striking, however, is that all publications on this subject used one-lung ventilation through a double-lumen endotracheal tube. The studies described the following risk factors: • Pulmonary hypertension • Administration of fresh frozen plasma (28)(29)(30).…”
Section: Anesthesia and Postoperative Care In Minimally Invasive Procmentioning
confidence: 99%
“…One study using DLV found a 7.9% incidence of UPE on CXR after MICs (defined as large-scale, ground-glass opacities), which was clinically relevant in 1.5% of patients, with prolonged postoperative ventilation up to 306.5 hours. 5 In studies using OLV for MICs, the incidence of postoperative UPE varied between 2.1% and 25%. 6À8 The considerable difference between studies probably is due to the different assessment criteria.…”
Section: Discussionmentioning
confidence: 99%
“…7,9) Recently, Keyl et al 8) described that 7.9% incidence of radiographically evident RPE after MICS. They reported that among total number of MICS patients, 1.5% developed clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Although mechanical stress and histologic abnormalities of the pulmonary microcirculation were reported as mechanisms of RPE, the risk factors after cardiac surgery with single-lung ventilation are still unknown. 8,15,16) It is well known that CPB induces a systemic inflammatory response called post-pump syndrome. Although some organs can be involved, the lung is often the first organ damaged, making this a major complication of CPB.…”
Section: Discussionmentioning
confidence: 99%